Avaliação comportamental, perfil oxidativo e atividade de ATPases e colinesterases em ratos expostos ao cádmio e tratados com quercetina - Abdalla, Fátima Husein (2014)
Cadmium (Cd) is considered one of the most toxic heavy metals for its ability to affect different tissues, including the brain and the immune system. The molecular mechanisms of toxicity of Cd are not well established, however, it is known that one of the consequences of Cd exposure is the generation of oxidative stress. Conversely, the quercetin, one flavonoid present in various foods performs various therapeutic functions in the body, such as antioxidant activity, anti-inflammatory and neuroprotective action. Thus, the aim of this study was to investigate the effects of quercetin on the behavioral tests, the activity of the enzymes acetylcholinesterase (AChE), Na+, K+-ATPase and the δ-dehydratase aminolevulinic acid (δ-ALA-D), as well as parameters of oxidative stress in the central nervous system of adult male wistar rats exposed to CdCl2. The activities of enzymes AChE, NTPDase and adenosine deaminase (ADA) of peripheral lymphocytes, butyrylcholinesterase (BuChE) in the serum and myeloperoxidase (MPO) in plasma were also measured in the peripheral system of these animals. The rats were exposed to CdCl2 (2.5 mg / kg) and quercetin (5, 25 or 50 mg / kg) by gavage (1 ml/kg) for 45 days. Hence, the animals were divided into eight groups (n = 10-14): saline/control, saline/Querc 5 mg/kg, saline/Querc 25 mg/kg, saline/Querc 50 mg/kg, Cd/ethanol, Cd/Querc 5 mg/kg, Cd/Querc 25 mg/kg and Cd/Querc 50 mg/kg. The groups treated with Cd and quercetin, received the antioxidant quercetin solution after 30 minutes of the administration of Cd solution. At the end of 45 days of the treatment the animals were submitted to training and behavioral tests. After, they were anesthetized by halothane inhalation, and blood collection was performed to set serum, plasma and peripheral lymphocytes apart. Then the animals were euthanized, with part of the brain being removed for analysis of the enzyme δ-ALA-D activity, while the other part of brain was dissected into, cerebral cortex, striatum, cerebellum, hippocampus and hypothalamus, for future enzymatic assays. The results showed that Cd is able to cross the blood brain barrier, therefore, although the amount of Cd accumulated in the different brain structures studied was low, it was significantly higher than in control. Simultaneous treatment of quercetin in Cd exposed animals was ineffective to decrease these levels of Cd. The Cd exposure caused impairment on learning and memory, besides causing an increase in the anxiogenic behavior type. Nevertheless, the treatment with quercetin prevented the undesirable effects caused by exposure to the metal in the anxiety and memory. In relation to enzymatic activities in the brain, it was observed that Cd exposure reduced AChE activity in cerebral cortex and hippocampus, while as activation of the enzyme was observed in hypothalamus. Furthermore, a decrease in the Na+, K+-ATPase enzyme activity in cerebral cortex, hippocampus and hypothalamus was observed, as well as a decrease in the δ-ALA-D activity in total brain of Cd exposed animals. Interestingly, the quercetin co-administration in the Cd exposed animals prevented the changes in the activity of the enzymes AChE and Na+, K+-ATPase in different brain structures, though has not restored the δ-ALA-D enzyme activity. It was also observed an increase in ROS production, in lipid peroxidation, in protein oxidation, the levels of double stranded DNA and changes in the antioxidant system, such as, reduction in the glutathione reductase (GR) activity, levels of total thiols (T-SH) and reduced glutathione (GSH), and an increase in the glutathione S-transferase (GST) enzyme activity in cerebral cortex, hypothalamus and hippocampus of Cd exposed animals. Co-administration of quercetin in Cd exposed rats was able to prevent totally or partially the changes caused by metal exposure in oxidative stress parameters. It is suggested that quercetin is able to reduce the oxidative damage caused by exposure to these metal and subsequently restore the AChE and Na+, K+-ATPase activities, modulating cholinergic neurotransmission and improving cognitive processes. In relation to the peripheral system, there was an increase in the NTPDase, ADA, AChE, BuChE and MPO activities in Cd exposed rats. Based on these results it is possible to infer that the increase in NTPDase activity is a compensatory effect due to the increase in ATP levels in circulation. It is suggested that decreased levels of ACh are available in the circulation due to increase in the peripheral cholinesterase activity. When rats were treated with the quercetin, flavonoid was able to modulate the activities of these enzymes probably due to the anti-inflammatory property of the compound. Accordingly, it is suggested that quercetin prevents or eases the toxicity caused by exposure to metal due to its antioxidant and anti-inflammatory activities. Therefore, it is believed that the flavonoid may be a promising drug in alternative therapies against toxicity induced by the metal in the central nervous system and peripheral system.